2011
DOI: 10.1093/cid/cir182
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Adjuvanted Monovalent Vaccine Against the 2009 Pandemic Strain of Influenza A(H1N1)v in Stockholm County, Sweden

Abstract: The monovalent AS03-adjuvanted influenza vaccine was highly effective in prevention of the pandemic influenza in Stockholm County. A single dose seemed to be sufficient in most, both children and adults, except in immunocompromised hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 20 publications
1
27
1
1
Order By: Relevance
“…Although the HAI assay only measured the phase of virus attachment to a host cell, the MN assay confirmed that vaccine-induced antibodies prevented viral infection. Thus, most cancer patients were likely protected against influenza A/H1N1/09, although T-cell responses were not assessed [30,31]. The high seroprotection and seroconversion rates observed in our study contrasted with recent data showing poor immune responses (i.e., seroprotection and seroconversion rates Ͻ50%) in cancer patients [26,32,33].…”
Section: Discussioncontrasting
confidence: 91%
“…Although the HAI assay only measured the phase of virus attachment to a host cell, the MN assay confirmed that vaccine-induced antibodies prevented viral infection. Thus, most cancer patients were likely protected against influenza A/H1N1/09, although T-cell responses were not assessed [30,31]. The high seroprotection and seroconversion rates observed in our study contrasted with recent data showing poor immune responses (i.e., seroprotection and seroconversion rates Ͻ50%) in cancer patients [26,32,33].…”
Section: Discussioncontrasting
confidence: 91%
“…Among other immunocompromised populations, primarily cancer patients and transplant recipients (individuals receiving hematopoietic stem cell or solid organ transplants), single doses of both unadjuvanted and adjuvanted inactivated influenza vaccines have solicited only moderate immunological responses in adults [269,[273][274][275][276][277][278][279] and children. [280][281][282] Many of these studies found that a second dose significantly improved the proportion achieving serological protection.…”
Section: Disease Burdenmentioning
confidence: 99%
“…However, a prospective population-based cohort study carried out in Stockholm County, Sweden indicated that the monovalent AS03-adjuvanted influenza vaccine was highly protective against pandemic influenza [23]. Other studies, using the same adjuvanted vaccine, have confirmed its efficiency [24,25]. On the other hand, countries with little vaccination efforts did not differ in influenza-caused morbidity or death compared with Sweden.…”
Section: Discussionmentioning
confidence: 99%